Study of Product Label Influence and Purchase Decision via Google Form and eBay Listing - Abd Rahman, Misbahul Muneer; Ibrahim, Danial (Multidisciplinary Applied Research and Innovation, 2021)
The purpose of this paper is to study the influence of four different product labels via Google Form and purchase decision by the global consumers via eBay listing. eBay is one of the biggest e-commerce platforms where product labelling highly influence purchase decision. A purposely developed questionnaire was administered to 90 randomly selected age between 18 and 64 years. The first part of the questionnaire sought information on socio-demographic profile, whereas the second part of the questionnaire had questions related to consumers’ perception of towards four different types of design developed. In addition to the survey, all four products were listed on eBay website. The product view and sold data were collected during a period of five months. The results of agree versus disagree in each four product designs indicated that more than 80 percent of respondents agreed that the product label influence their purchase decisions. Based on the findings of this study, it can be safely concluded that customers do perceive the importance of product labelling and read it before making their purchase decisions. It is expected that the findings of this study will help manufacturer to devise appropriate strategies to make labels more useful and effective tool of communication towards influencing purchase decisions of potential customers